갱년기 여성의 건강증진 생활양식, 자기효능, 가족기능, 폐경증상의 관계연구 - 장혜숙; 김영희; 서영숙; 김효순; 문명희; 옥루수; Jang, Hye-Sook; Kim, Young-Hee; Suh, Young-Sook; Kim, Hyo-Soon; Moon, Myung-Hee; Ok, Ru-Th (여성건강간호학회지, 2000)
The purpose of this study was to provide basic data for developing a nursing intervention for climacteric women by describing a health promoting lifestyle. Also this study identified the relationship between self-efficacy and family function which are factors affecting the health promoting behaviors. The subjects of this study were 143 women from 40 to 59 years of age. The data was analyzed using SPSS program for t-test, ANOVA, and Pearson's correlation coefficients. The results of the study are as follows; 1. The average score of performance in the health promoting lifestyle was 2.82. The variable with the highest degree of performance was the sanitary environment and reconciliatory relationship(3.31), whereas the one with the lowest degree was the professional health maintenance(2.27). The average score of self-efficacy was 71.44, family function was 68.50, and menopausal symptoms was 60.30. 2. There was a statistically significant difference in performance in health promoting lifestyle according to satisfaction of marital life. Also there was a significant difference between self-efficacy, religion, and family function. 3. Performance in the health promoting lifestyle was positively related to self-efficacy, and family function and negatively related to menopausal symptoms. Self-efficacy was positively related to family function. In conclusion, performance in health promoting lifestyle was related to self-efficacy, family function and menopausal symptoms. These factors were affected by religion, family type, and satisfaction of marital life. Therefore, health promoting programs to increase climacteric women's health should be a planed program based on results of this study.